Efficacy of therapist-supported online remote behavioral therapy for tic disorders: a systematic review and meta-analysis - Xu, Xiaolei; Zhu, Kangsheng; Wang, Weiyi; Zhao, Tianyu; Fu, Congrui (Frontiers in Psychiatry, 2025)
IntroductionRecently, several studies about therapist-supported online remote behavioral therapy (TSORBT) have been showed effective for tic disorders (TD). With the increasing adoption of telemedicine, a systematic review of existing evidence is crucial to confirm the efficacy of TSORBT in treating TD.AimWe aim to assess the efficacy of TSORBT on the treatment of TD.MethodThis review followed PRISMA guidelines. We searched PubMed, Web of Science, Cochrane, and Embase up to September 2024 for clinical trials on TSORBT’s efficacy in TD. Two researchers independently screened studies, focusing on the Total Tic Severity Score of the Yale Global Tic Severity Scale (YGTSS-TTSS) and other subscores of the YGTSS-motor tic score (YGTSS-MTS), YGTSS-vocal tic score (YGTSS -VTS), YGTSS-impairment score and Parent Tic Questionnaire (PTQ). Risk of bias was assessed using Cochrane RoB 2. Data were analyzed in RevMan 5.4, with outcomes expressed as mean difference (MD) and 95% CI.ResultsIn total, 2764 articles were identified for screening. Nine studies involving 1049 participants, with 527 assigned to the TSORBT and 522 to the control were included. TSORBT exhibited potential in addressing YGTSS-TTSS (MD = -2.22, 95% CI: [-3.16, -1.29], P<0.00001), YGTSS-MTS (MD = -2.17, 95% CI: [-3.39, -0.96], P=0.0004), YGTSS-impairment score (MD= -1.69, 95% CI: [-3.26, -0.12], P=0.03) and PTQ score (MD= -6.05, 95% CI: [-8.65, -3.44], P<0.00001);. Subgroup analyses revealed that TSORBT demonstrated nearly the same efficacy as face-to-face BT in addressing YGTSS-TTSS (MD = -0.38, 95% CI: [-3.20, 2.43], P=0.79), but more effective than online psychoeducation (MD = -2.37, 95% CI: [-3.64, -1.10], P = 0.0002).ConclusionThe current study demonstrates the promising therapeutic efficacy of TSORBT in TD. Further rigorously designed studies, particularly those assessing long-term treatment durability, are warranted to consolidate the evidence base.